Physico-Chemical and Sensory Evaluation of Chicken Nuggets with Cooked Unripe Plantain - Selvakumar, K; Anandh, M Anna; Rajarajan, G; Ilavarasan , R; Sangeetha, A (Journal of Meat Science, 2024)
Chicken nuggets were prepared with 5%, 10%, and 15% steam cooked unripe plantain without peel, and their qualities were evaluated. Linear and significantly (P < 0.01) increased values were observed for emulsion stability, cooking yield, moisture retention, fat retention, moisture, and total ash contents. Conversely significantly (P<0.01) reverse trends were observed for emulsion pH, product pH, protein and fat contents. Fiber content values were significantly increased from0.46±0.03 to 5.71±0.08%. Sensory evaluation done using nine point hedonic scale indicated that 10% cooked unripe plantain without peel resulted in higher scores for appearance, colour, flavor, juiciness, tenderness, texture and overall acceptability among the three treatments. Thus, it can be concluded that, 10% cooked unripe plantain without peel can be successfully used for preparation of fiber enriched functional chicken nuggets of acceptable quality.